Advancement in utilization of magnetic catalysts for production of sustainable biofuels - Zhang, Yutao; Li, Weihua; Wang, Jialu; Jin, Jiaxing; Zhang, Yixi; Cheng, Jingsong; Zhang, Qiuyun (Frontiers in Chemistry, 2023)
In this study, we summarize recent advances in the synthesis of magnetic catalysts utilized for biodiesel production, particularly focusing on the physicochemical properties, activity, and reusability of magnetic mixed metal oxides, supported magnetic catalysts, ionic acid-functionalized magnetic catalysts, heteropolyacids-based magnetic catalysts, and MOFs-based magnetic catalysts. The prevailing reaction conditions in the production of biodiesel are also studied. Finally, the current limitations and future challenges for future research needs in the magnetic catalyst study have been given.